Acceptability and usability of a paediatric HIV screening tool in high-volume outpatient settings in Malawi, perspectives from caregivers and healthcare workers. Issue 1 (7th March 2023) - Katirayi, Leila; Maphosa, Thulani; Kudiabor, Kwashie; Kayira, Dumbani; Gross, Jessica; Hrapcak, Susan; Chamanga, Rachel; Nkhoma, Harrid; Puleni, Paul; Maida, Alice; Ahimbisibwe, Allan; Woelk, Godfrey
Abstract : Background: Using an HIV pretest screening tool to identify children most at risk for HIV infection may be a more efficient and cost-effective approach to identify children living with HIV in resource-limited settings. These tools seek to reduce overtesting of children by increasing the positive predictive value while ensuring a high negative predictive value for those screened for HIV. Methods: This qualitative study in Malawi evaluated acceptability and usability of a modified version of the Zimbabwe HIV screening tool to identify children aged 2–14 years most-at-risk. The tool included additional questions about previous hospitalisations due to malaria and prior documented diagnoses. Sixteen interviews were conducted with expert clients (ECs), trained peer-supporters, which administered the screening tool and 12 interviews with biological and non-biological caregivers of screened children. All interviews were audiorecorded, transcribed and translated. Transcripts were analysed manually using a short-answer analysis, compiling responses for each question by study participant group. Summary documents were generated, identifying common and outlier perspectives. Results: The HIV paediatric screening tool was generally accepted by caregivers and ECs, with both groups seeing the benefit of the tool and promoting its use. The ECs who were primarily responsible for implementing the tool initially struggled with acceptance of the tool but started to accept it after additional training and mentorship was provided. Overall, caregivers accepted having their children tested for HIV, although non-biological caregivers expressed hesitancy in giving consent for HIV testing. ECs reported challenges with the ability for non-biological caregivers to answer some questions. Conclusion: This study found general acceptance of paediatric screening tools in children in Malawi and identified some minor challenges that raise important considerations for tool implementation. These include the need for a thorough orientation of the tools for the healthcare workers and caregivers, appropriate space at the facility, and adequate staffing and commodities.